2023
DOI: 10.3390/ma16082944
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Flank Wear on the Microstructure Characteristics of the GH4169 Metamorphic Layer under High-Pressure Cooling

Abstract: Since the flank has an important influence on the surface of a workpiece, and as microstructure flaws of the surface metamorphic layer are a key factor that affects the service performance of a part, this work studied the influence of flank wear on the microstructure characteristics of the metamorphic layer under the conditions of high-pressure cooling. First, Third Wave AdvantEdge was used to create a simulation model of cutting GH4169 using tools with different flank wears under high-pressure cooling. The si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…This phenomenon can be attributed to the reduction in tool clearance angle caused by flank wear, which in turn enlarges the contact area between the flank and the workpiece surface. Consequently, increased friction in the contact region leads to higher cutting forces [28]. This is even more important when considering the machining of the UNS S32750 alloy due to its low thermal conductivity and susceptibility to strain hardening.…”
Section: Cutting Forcesmentioning
confidence: 99%
“…This phenomenon can be attributed to the reduction in tool clearance angle caused by flank wear, which in turn enlarges the contact area between the flank and the workpiece surface. Consequently, increased friction in the contact region leads to higher cutting forces [28]. This is even more important when considering the machining of the UNS S32750 alloy due to its low thermal conductivity and susceptibility to strain hardening.…”
Section: Cutting Forcesmentioning
confidence: 99%
“…The results showed that high-pressure cooling can reduce the wear of the tool rake face caused by chip plastic side flow. Wei et al [29] found that by studying the influence of tool wear on the microstructure of the metamorphic layer under high-pressure cooling conditions, with the increase of flank wear width, the cutting force, cutting temperature, plastic strain, and strain rate showed a significant upward trend. Zhang et al [30] found through experimental research on cutting GH4169 under high-pressure cooling that the degree of influence of cutting amount and coolant pressure on tool vibration was in order of feed speed, cutting depth, cooling pressure, and cutting speed.…”
Section: Introductionmentioning
confidence: 99%